2022
DOI: 10.1287/msom.2020.0947
|View full text |Cite
|
Sign up to set email alerts
|

Product Price, Quality, and Service Decisions Under Consumer Choice Models

Abstract: Problem definition: In this paper, we develop an integrated framework to study a firm’s joint decisions on product price, quality, and service duration in a variety of monopolistic and competitive scenarios. Academic/practical relevance: Product price, quality, and ancillary service (such as maintenance and factory warranty) are arguably among the most important factors consumers consider when making a purchase decision. Meanwhile, they are also seen as effective instruments for firms to achieve market segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Product price is one of the most important factors consumers consider when making a purchase decision ( Wang et al, 2022 ). Interestingly, this study shows that users tend to have more positive attitude with higher perceived price, which is different from previous findings on the effect of price on user attitudes in traditional shopping settings ( Chao and Liao, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Product price is one of the most important factors consumers consider when making a purchase decision ( Wang et al, 2022 ). Interestingly, this study shows that users tend to have more positive attitude with higher perceived price, which is different from previous findings on the effect of price on user attitudes in traditional shopping settings ( Chao and Liao, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latent-class-based model was applied to a real-life consumer electronic pricing optimization case, and significant performance improvement of the manufacturer was observed. From another perspective, the authors in [5] studied an integrated product design problem whereby a firm jointly determines multiple product attributes, e.g., price, quality and service duration. It is shown that such product differentiation can both benefit the consumers and improve the profitability of the firm.…”
Section: B Analysis Methods In Product and Service Designmentioning
confidence: 99%
“…This conforms to [30] consideration of the concept of quality as an elusive concept that is distinct and complex which is often mistaken with other related concepts. Quality can be categorized in terms of various perspectives like Judgement, product, user, value, or manufacturing perspective [53] Judgmentally, the quality of a product is not easily defined but a person can identify it once he comes across it. The user perspective is about how the needs of a user of a particular product are met.…”
Section: Literaturementioning
confidence: 99%